Az örvény - Forgács, Péter (Hungary : For-Creation Bt., 1996)
Free fall reflects to the times before the Shoah, the darkest chapter of the 20th century Hungary, based on the home movies of the talented musician, photographer and businessman, György Pető who made 8mm films from 1938. We follow their story, to discover what's behind the Pető’s happiness, how they suppress the fearful signs of threatening evidences of forthcoming massacres. Free Fall envisions the illusions of a Jewish Hungarian family eroded step by step, the happy, banal moments framed by the Hungarian Jewish laws. How do we understand segregation, the racist laws if ‘angels’ voice recites them? We follow their determination, the unpredictable events, and their illusions, and hopes until the very last moments. The Free Fall video opera recitative music composed and conducted by Tibor Szemző.
Keywords: Documentary films